กลยุทธ์การประชาสัมพันธ์และประสิทธิผลของโครงการรณรงค์แยกประเภทขยะ ของสำนักรักษาความสะอาด กรุงเทพมหานคร - พิมพ์ใจ ปัทมสันติวงศ์ (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
The main objective of this research was to study the strategies used in public relations and communication campaign of waste sorting. Its effectiveness was also examined through assessing sample s exposure to this campaign, awareness toward the waste sorting, and disposing behavior. Questionnaires were used to collect data from the Bangkok inhabitants selected 400 samples. The result of the study revealed that the principal strategies were to publicize the campaign s spot and information through the mass media, and the main media was television, radio, newspaper, the Public Cleansing Department s journals, and the specialized media such as campaign boards, poster and brochure in order to conduct the awareness, the familiarity with its symbolic logo and waste sorting behavior to the intended receivers. The result of the assumption were as follows: 1. Exposure to the campaign s spot and information was correlated with the awareness of waste sorting behavior. 2. Exposure to the campaign s spot and information was correlated with the waste sorting behavior. 3. The awareness of waste sorting was correlated with the waste sorting behavior.